Caspofungin versus anidulafungin in patients with invasive candidiasis: a retrospective study with propensity-score-matched analysis - Reem Hasan Elajez; Dana Bakdach; Sara Al Balushi; Ahmed Zaqout; Rand Alattar; Tasneem Abdallah; Waleed Awouda; Godwin Wilson; Walid Al-Wali; Emad Ibrahim; Hussam Alsoub (Therapeutic Advances in Infectious Disease)
Background: Echinocandins are recommended as an initial treatment for invasive candidiasis. Although safety and efficacy profiles of both anidulafungin and caspofungin are well established, direct head-to-head comparisons have not been reported before. Objective: Compare efficacy and safety of anidulafungin versus caspofungin among patients with invasive candidiasis. Design: Retrospective observational study. Methods: Adult patients with invasive candidiasis who were treated with either anidulafungin or caspofungin for ⩾5 days were retrospectively reviewed over a period of 6 years. The primary endpoint was global response, defined as clinical and microbiological success at the end of treatment duration. Results: A total of 223 patients who received either anidulafungin ( n  = 176) or caspofungin ( n  = 47) were initially included. Propensity score matching (based on age, malignancy, level of care, presence of candidemia, and other factors) was performed to improve comparability of the two groups. As a result, 32 patients in the caspofungin arm and 79 patients in the anidulafungin arm were included in the final analysis. Around three-quarters of the cohort had candidemia, and the most common isolated Candida species were C. albicans and C. glabrata . Response rates were comparable between both groups, with the primary outcome of global response showing no significant difference (56.3% for the caspofungin group vs 63.3% for anidulafungin, p  = 0.490). Similarly, no differences between the two groups were observed in terms of 90-day all-cause mortality ( p  = 0.672) or any other secondary endpoints. Conclusion: Our data suggest that anidulafungin and caspofungin have comparable global response among patients with invasive candidiasis. Additionally, both studied echinocandins showed no significant difference in 90-day all-cause mortality. However, due to the limited sample size, larger studies are needed to confirm these results.